Persuasiveness in political discourse on Twitter - Goroshko, Olena; Poliakova, Tetiana (ФОП Домбровська Я. М., 2018)
The article focuses on the question of new communication form appearance – the internet communication, namely political internet communication, that furthermore influenced the appearance of the new genres, among which we can find twitting. The active twitting usage with the communicative aim in political sphere puts the question about language learning namely about the means of expression of the persuasive language influence in the analyzed genre, as the persuasive language influence function is one of the most important functions in political internet-communication from psycholinguistic point of view. The research process found out the range of verbal expression meanings of explicit and implicit persuasiveness. To the verbal meanings of implicit persuasiveness, we can refer the usage of imperatives and imperative constructions, explicit performatives, constructions with modal verbs, short sentences, and slogans. The verbal meanings of implicit persuasiveness include rhetorical questions, affirmative sentences, and famous people’s citations. To the special language meanings, which encourage the influence on the addressee we also refer the usage of elliptical sentences, parcelation, repetition. The mostly used lexical and stylistic meanings, that encourage the fulfillment of the main purposes of political discourse is the usage of metaphor, metonymy, irony, personification and oxymoron. The research allowed us to come to conclusion, that the English-speaking political internet-communication is characterized with the usage of the same verbal appellation meanings as traditional communication. But we can also outline the meanings peculiaronly to the internet communication and especially the twitting genre. For the research methodology we took out modern scientific conceptions. The research methodology was developed according the framework of genre study, psycholinguistics 2.0, virtual genre study. According to the aim and tasks, general and linguistic research methods were used.

Стаття присвячена питанням появи нової форми комунікації – інтернет-комунікації, а саме політичної інтернет-комунікації, що, в свою чергу, призвело до виникнення нових жанрів, одним з яких є твіттінг. Активне використання твіттінга з метою комунікації в політичній сфері ставить питання про вивчення мови, а саме – способів вираження персуазивності в досліджуваному жанрі, оскільки функція персуазивного мовного впливу є однією з найважливіших функцій політичної інтернет-комунікації з точки зору психолінгвістики. У процесі дослідження було виявлено ряд вербальних засобів вираження експліцитної та імпліцитної персуазивності. До вербальних засобів експліцитної персуазивності можна віднести використання імперативів та імперативних конструкцій, експліцитних перформативів, конструкцій з модальними дієсловами, коротких речень, слоганів. Вербальні засоби імпліцитної персуазивності включають в себе риторичні запитання, стверджувальні речення, цитування висловів відомих особистостей. До спеціальних мовних засобів, що підсилюють вплив на адресата, також відносять використання еліптичних речень, парцеляції, повтору. Найбільш частотними лексичними стилістичними засобами, які сприяють досягненню основних цілей політичного дискурсу, є використання метафори, метонімії, іронії, уособлення і оксиморона. Дослідження дозволило зробити висновок, що англомовна політична інтернет-комунікація характеризується використанням тих же вербальних засобів апелювання, що і традиційна комунікація. Однак можна також виділити засоби, властиві виключно інтернет-комунікації, а саме жанру твіттінг. Методологічною базою дослідження слугували сучасні наукові концепції, розроблені в рамках жанрознавства, психолінгвістики 2.0, віртуального жанрознавства. Відповідно до поставленої мети і завдань були використані як загальнонаукові, так і лінгвістичні методи дослідження.
Персуазивність у жанрі твіттінг в англомовному політичному дискурсі
Keywords: psycholinguistics 2.0; political internet communication; internet-genre; twitting; persuasiveness; психолінгвістика 2.0; політична інтернет-комунікація; інтернет-жанр; твіттінг; персуазивність